Conditioned Medium From the Stem Cells of Human Exfoliated Deciduous Teeth Ameliorates Neuropathic Pain in a Partial Sciatic Nerve Ligation Model - Liu, Yao; Kano, Fumiya; Hashimoto, Noboru; Xia, Linze; Zhou, Qiao; Feng, Xingmei; Hibi, Hideharu; Miyazaki, Aya; Iwamoto, Tsutomu; Matsuka, Yoshizo; Zhang, Zhijun; Tanaka, Eiji; et al. (Frontiers in Pharmacology, 2022)
In neuropathic pain (NP), injury or diseases of the somatosensory system often result in highly debilitating chronic pain. Currently, there is no effective drug for the complete and definitive treatment of NP. We investigated the therapeutic potential of conditioned medium (CM) derived from stem cells from human exfoliated deciduous teeth (SHED-CM) against NP using a mouse partial sciatic nerve ligation (PSL) model. Abnormal pain sensation, such as tactile allodynia and hyperalgesia, can be caused by PSL. In the behavioral test, intravenous administration of SHED-CM greatly improved the PSL-induced hypersensitivity. We found that treatment with SHED-CM resulted in the recruitment of M2 macrophages in the injured sciatic nerve and ipsilateral L4/L5 dorsal root ganglion and suppressed microglial activation in the spinal cord. Notably, speciﬁc depletion of the anti-inﬂammatory M2 macrophages by mannosylated-Clodrosome markedly reduced the antinociceptive effect of SHED-CM. Intravenous administration of CM from M2 induced by SHED-CM (M2-CM) ameliorated the PSL-induced hypersensitivity. We found that M2-CM directly suppressed the expression of nociceptive receptors as well as proinflammatory mediators in Schwann cells. Taken together, our data suggest that SHED-CM ameliorates NP through the induction of the analgesic anti-inflammatory M2 macrophages. Thus, SHED-CM may be a novel therapeutic candidate for NP.